Pojmy daʿwa a džihád v klasickém islámu = The concept of daʿwa and jihad in the classical Islam - Mendel, Miloš (Religio, 1995)
Trying to examine the contemporary and recent expressions of Islamic religion in the social and political sense, it seems to be highly relevant to understand the semantic content of terms and notions which occur most frequently in both the Islamic religio-ideological texts and the ordinary political rhetoric of ruling regimes. The author of the paper deals with two of the key terms of classical Islam mostly used in various forms of contemporary Islamic reformism. The first term - daʿwa- is analysed in its religious and historical context. The author reminds the variability of its content all over the Islamic history. Then, he binds the notion of daʿwa (mostly in the sense of God's will, revelation etc.) with that of classical notion of jihad, which should be also understood in its multiform content as the means of promotion of daʿwa. The author stresses that the methodology of "semantic archeology" represents one of the possible and effective approaches to the correct understanding of any thoroughly structured religious system, though such an approach might be full of obstacles caused by the unavoidable rate of subjectivism. But still, the method of content analysis and examination of semantic variations in the context of history, provides us, at least in the case of Islam, with a good number of informations reliable and useful for studying the complicated mozaic of contemporary Islamic thought.